Pengaruh Green Business dan Good Corporate Governance Terhadap Kinerja Keuangan: Corporate Social Responsibility sebagai Pemoderasi - Andi Aris Mattunruang; Asmirawati Asmirawati (Owner : Riset dan Jurnal Akuntansi, 2023)
The aim of this study was conducted to find out whether green business using the annual reports of companies that received the Pollution Control, Evaluation and Ranking Program Award (PROPER) corporate social responsibility is influenced by the characteristics of the board of commissioners (number of independent commissioners, diversity of the board of commissioners, and concentration of ownership) and whether financial performance (ROA, ROE and Tobin's Q) is moderated by corporate social responsibility, in companies listed on the Indonesia Stock Exchange in the period 2015 to 2022. The population used is all companies listed on the Stock Exchange Indonesia for five consecutive years. The sampling method was selected using purposive sampling, namely non-financial companies included in Pefindo 25. This study used a quantitative approach. The samples used in this study were 22 companies with 110 observations. The data analysis method uses panel data regression (Eviews 9) with Descriptive Statistical Tests, Model Conformity Tests, namely the Chow test and Hausman test, followed by the F test, the Goodness of Fit test, the hypothesis test, and finally the t test. The results of research on green economy and good corporate governance which are proxied by the number of independent commissioners, the diversity of the board of commissioners and the majority ownership of the company have a positive effect on financial performance. moderated by corporate social responsibility has no positive effect on financial performance proxied by ROA, ROE and leverage.